2013
DOI: 10.1095/biolreprod.113.113142
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Disturbance of DNA Methylation in the Uterine Decidua in the CBA/J × DBA/2 Mouse Model of Pregnancy Failure1

Abstract: Nonchromosomal pregnancy failure is a common but poorly understood phenomenon. Because recent data have suggested that epigenetic abnormalities such as abnormal placental DNA methylation may play a role in human pregnancy failure, we undertook experiments to test whether decidual and/or placental DNA methylation abnormalities are present in a mouse model of pregnancy failure. A large number of studies have shown that crosses between CBA/J female mice and DBA/2 males result in pregnancies with a high rate of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In one study, Brown and colleagues showed that abnormal DNA methylation in the uterine decidua (but not placenta) likely plays a role in the CBA/J × DBA/2 murine model of pregnancy failure (Brown et al 2013). In addition, elegantly designed ovarian transplant experiments in 15 inbred strains of mice showed a wide variation of gestation length between (but not within) strains.…”
Section: There Is a Genetic Predisposition For Preterm Birth That Is mentioning
confidence: 99%
“…In one study, Brown and colleagues showed that abnormal DNA methylation in the uterine decidua (but not placenta) likely plays a role in the CBA/J × DBA/2 murine model of pregnancy failure (Brown et al 2013). In addition, elegantly designed ovarian transplant experiments in 15 inbred strains of mice showed a wide variation of gestation length between (but not within) strains.…”
Section: There Is a Genetic Predisposition For Preterm Birth That Is mentioning
confidence: 99%
“…A number of studies have shown that crosses between CBA/J female mice and DBA/2 males result in pregnancies with a high rate of failure/resorption, whereas other crosses with CBA/J females produce normal pregnancies (13)(14)(15). All studies were performed with the approval of the University of Inner Mongolia Institutional Animal Care and Use Committee.…”
Section: Mouse Model Of Pregnancy Failurementioning
confidence: 99%
“…The negative effects of 5-aza-dC on decidualization is also supported by another study using a mouse model (68). Recently, appreciable differential methylation on a single chromatin is uncovered comparing fertile and infertile decidua from genetically different mice (73). There is considerable discrepancy between the aforementioned studies in humans and mice on regulation of DNMTs expression and the effects of DNA methylation inhibitor.…”
Section: Dna Methylation and Uterine Decidualizationmentioning
confidence: 99%